Young video game players’ self-identified toxic gaming behaviour: An interview study - Ruotsalainen, Maria; Meriläinen, Mikko (Eludamos: Journal for Computer Game Culture, 2023)
In this study we analyze negative behaviour in the context of digital gaming through interviews of players (N=12) aged 16–27 who self-reported as having behaved in a manner they acknowledged as toxic. Through thematic analysis of the interviews, we highlight three central themes: Games as affective spaces; affordances and norms facilitating negative behaviours; and players’ navigation of negative behaviours. Our study demonstrates the situational and affective nature of negative behaviour and offers solutions for reducing it in gaming.